Crystal structure of 4-bromo-3-nitro-1H-pyrazole-5-carboxylic acid monohydrate, C4H2N3BrO4·H2O - Radović Ana; Giester Gerald; Tomić Zoran D.; Kočović David; Jaćimović Željko K. (Zeitschrift für Kristallographie - New Crystal Structures)
C4H2N3BrO4·H2O, monoclinic, P21/c (no. 14), a = 7.177(2) Å, b = 10.999(3) Å, c = 10.414(3) Å, β = 100.145(11)∘$100.145{(11)}^{° }$, V = 809.3(4) Å3, Z = 4, Rgt${R}_{gt}$(F) = 0.0379, wRref$wR_{ref}$(F2) = 0.0714, T = 200 K